Biogas Purification by Adsorption Method Using Activated Carbon and Zeolite Adsorbents - Fitrah Fourqoniah; Leila Kalsum; Selastia Yulianti (Equilibrium Journal of Chemical Engineering, 2023)
Abstract. Biogas is an alternative energy that is formed from the fermentation of organic matter in gaseous form. Biogas consists of several gas mixtures with the main components methane (CH4) and carbon dioxide (CO2) with a small amount of steam. Biogas is an alternative technology that produces environmentally friendly, cheap and renewable fuel because it comes from biomass, organic liquid waste, food scraps, organic waste, leaves and animal manure resulting from the fermentation process. This study aims to purify biogas by adsorption method using activated carbon and zeolite adsorbents to obtain optimal methane gas by varying the biogas flow rate and the amount of adsorbent composition. Variation in the ratio of the amount of adsorbent (activated carbon: zeolite) is 0%:100%, 30%:70%, 50%:50%, 70%:30%, 100%:0% and the flow rate variation used is 0.2 liter/minute, 0.4 liter/minute, and 0.6 liter/minute. From the purification results, an analysis of the gas content contained in the biogas was carried out using a gas analyzer. The results showed that the best flow rate was the smallest flow rate, which was 0.2 liter/minute, and the best variation in the amount of adsorbent was 0%:100% adsorbent (activated carbon: zeolite) with 81.40% methane content.Keywords:Biogas, Activated Carbon, Zeolite, Adsorption, Purification,